Multifunctional and Dual-Responsive Polymersomes as Robust Nanocontainers: Design, Formation by Sequential Post-Conjugations, and pH-Controlled Drug Release - Iyisan, Banu; Kluge, Joerg; Formanek, Petr; Voit, Brigitte; Appelhans, Dietmar (Chemistry of Materials, 2016)
Robust, multiresponsive, and multifunctional nanovesicles are in high demand not only as carrier systems but also for applications in microsystem devices and nanotechnology. Hence, multifunctional, pH-responsive, and photo-cross-linked polymersomes decorated with adamantane and azide groups are prepared by mixed self-assembly of suitably end-modified block copolymers and are used for the subsequent postconjugation of the polymersome surface by using covalent and noncovalent approaches. For the covalent approach, nitroveratryloxycarbonyl-protected amine (NVOC) molecules as light-responsive moieties are introduced into the polymersomes through an azide-alkyne click reaction. After photocleavage of NVOC units, functional dye molecules react with the now freely accessible amine groups. The noncovalent approach is performed subsequently to introduce further moieties, making use of the strong adamantane-β-cyclodextrin host-guest interactions. It is quantitatively proven that all reactive groups have sufficient accessibility as well selective and orthogonal reactivity throughout these stepwise processes to allow the successful establishment of aimed pH- A nd light-responsive multifunctional polymersomes. Moreover, this sequential methodology is also applied to obtain doxorubicin-loaded multifunctional polymersomes for an efficient pH-controlled drug release. Overall, tunable membrane permeability combined with the potential for introducing multiple targeting groups by light-exposure or host-guest interactions make these smart polymersomes promising nanocontainers for many applications.
CRIS-Team Scopus Importer:2023-03-20